KONTRIBUSI CARA BELAJAR TERHADAP HASIL BELAJAR MATA DIKLAT MENGGAMBAR KONSTRUKSI TANGGA SISWA KELAS XI KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN DI SMK NEGERI 2 PADANGSIDIMPUAN - Ilham Satria Tambunan; Risma Apdeni, ST, MT (Universitas Negeri Padang, 2019)
Abstract - This study aims to reveal the contribution of the way of learning towards the learning outcomes of Stairs Construction Drawing course of Class XI students of Building Drawing Engineering at SMKN 2 Padangsidimpuan. The population was 40 students of Class XI of Building Drawing Engineering at SMKN 2 Padangsidimpuan. Sample was taken by using total sampling technique. Primary data were obtained from questionnaires containing statements about learning method that were distributed to respondents. Secondary data in the form of learning outcomes were obtained from teachers of the course. Data analysis techniques used are: (1) descriptive analysis, (2) test of analysis requirements, and (3) hypothesis test. From the results of this study it can be concluded that there is a contribution of the way of learning towards the learning outcomes of Stairs Construction Drawing course of Class XI students of Building Drawing Engineering at SMKN 2 Padangsidimpuan. The value of the contribution is 19.80%.Keywords: contribution, Way of learning, learning outcome